Museum As a Laboratory of Past Education - ., Bustan; ., Jumadi; Malihu, La; ., Bahri (KnE Social Sciences, 2024)
The past with its various narratives and legacies is something that is very important as a reinforcement of national identity. Museum as a place to store objects from the past, can describe historical reality for current and future generations. Miniature of historical heritage whose form describes the reconstruction of the past as well as the original remains of the culture of the people will only be obtained and can be studied in museums as a place to collect the world of the past for the people in all aspects. Thus, the existence of the museum as a reinforcement for understanding the past more closely in this case should be an important thing in developing the character of today’s nation’s children. This study uses a qualitative approach by collecting data through interviews, observation, and literature studies. The data that has been collected was then analyzed and presented in the form of an analytical descriptive description. Keywords: museums, learning resources, past education